Producer of controversy : Stanley Kramer, Hollywood liberalism and the Cold War - Frost, Jennifer (University Press of Kansas, 2017)
Through his career, politics, and films, Hollywood filmmaker Stanley Kramer significantly shaped American culture during the Cold War.
Introduction: "the thinking man's producer" -- A Hollywood independent -- Civil rights meets The defiant ones -- Nuclear war On the beach -- Inherit the wind champions civil liberties -- Holocaust history in Judgment at Nuremberg -- Cinematic diplomacy in Cold War Moscow -- An old liberal in new Hollywood -- Conclusion: legacies of a Hollywood liberal.
Print version record.
JSTOR
Keywords: Kramer, Stanley -- Criticism and interpretation; Kramer, Stanley; Politics in motion pictures; Politique au cinéma.; PERFORMING ARTS -- Film & Video -- History & Criticism; Politics in motion pictures; Electronic books; Criticism, interpretation, etc